WOMEN’S MAJELIS TAKLIM AND THE GRADUAL MOVE TOWARD GENDER EQUALITY (JOURNAL OF INDONESIAN ISLAM, 2023)
This article traces the history of Majelis Taklim groups in Indonesia since their emergence and reviews the groups’dynamics in the local Jambi region. Alongside the rise of Majelis Taklim, it details the advancement of women’s roles in the public sphere and their contributions to a functioning democracy. I argue that the role of Majelis Taklim groups has changed in recent decades, with the groups providing a vehicle for Muslim women’s interests and voices to be heard. In particular, women in Majelis Taklim groups are showing much more awareness of political issues compared to the past. Changes have occurred in wider Indonesian society, most significantly their participation in education since the 1960s. This is reflected in the gradual improvement in the Gender Equality Index and Human Development Index of Jambi in 2019 when compared to nearly a decade earlier in 2010, however, gender inequality issues, mainly regarding labor and political participation, are still strong.